Використання гетеродинної лазерної системи для визначення параметрів турбулентної атмосфери - Vildanov, R.; Eshonqulov, G. (Publishing house "Academperiodika", 2022)
The use of a heterodyne laser system in atmospheric measurements has been proposed. The continuous registration of optical phase variations of radiation propagating in the atmospheric channel has been carried out. From recorded data, the integral characteristics of a turbulence state in the radiation propagation channel are obtained.